The Maldivian Islamic education teachers' beliefs and use of innovative instructional approaches in teaching Islamic curriculum - Haneefa, Aminath (Kulliyyah of Education, International Islamic University Malaysia, 2021)
This study examined lower secondary Islamic Education teachers’ beliefs and use of innovative instructional approaches in teaching Islamic curriculum. It is a quantitative study conducted in Maldives involving 194 lower secondary Islamic Education teachers. Adapted two-part questionnaire was used to examine teachers’ beliefs and use of innovative instructional approaches in teaching Islamic curriculum. It is made up of ten subscales; static or dynamic, easy or hard, sanctity of the discipline, students’ learning and achievement, teacher’s role as a mentor, freedom of opinion, acceptance of innovation, innovation in the content of the Islamic curriculum, innovation in the method of teaching and innovation in the method of assessment and two overall scales; overall belief scale and use of innovative approaches scale. The outcomes of this study exposed that most of the teachers tend to have very strong belief regarding teacher’s role as a mentor. Also, they have strong belief about the sanctity of the discipline and students’ learning and achievement. However, teachers had moderate beliefs about static-dynamic and easy-hard nature of Islamic curriculum. The results of teachers’ use of innovative instructional approaches showed that teachers’ overall use of innovative instructional approaches in teaching Islamic curriculum is very high. Furthermore, this study also showed that there is no gender difference in beliefs and use of innovative instructional approaches. However, a significance difference was found between level of qualification and years of teaching experience and some scales of beliefs and use of innovative instructional approaches. Another major finding of the study is that there is a moderate positive correlation between beliefs and use of innovative instructional approaches.